Hydrodynamics and transport processes of inverse bubbly flow - Majumder, Subrata Kumar (Elsevier, 2016)
Hydrodynamics and Transport Processes of Inverse Bubbly Flow provides the science and fundamentals behind hydrodynamic characteristics, including flow regimes, gas entrainment, pressure drop, holdup and mixing characteristics, bubble size distribution, and the interfacial area of inverse bubble flow regimes. Special attention is given to mass and heat transfer. This book is an indispensable reference for researchers in academia and industry working in chemical and biochemical engineering. Hydrodynamics and Transport Processes of Inverse Bubbly Flow helps facilitate a better understanding of the phenomena of multiphase flow systems as used in chemical and biochemical industries.